Risk Management From The Perspective Of Islamic Economics: Case Study Of Swalayan Al-Fatih, Sumenep Regency - Hanifah Fauziyah; Jannatul Firdaus; Hertin Khalifatun Nisa Arifah; Any Sani’atin; Nurul Hidayat (International Forum of Researchers and Lecturers, 2024)
This article discusses risk management from the perspective of Islamic economics, with a case study on Swalayan Al-Fatih in Sumenep Regency. The research was conducted to address several issues, including: 1) What are the internal and external risks faced by Swalayan Al-Fatih in its daily operations? 2) What risk mitigation strategies can be implemented by Swalayan Al-Fatih from the perspective of Islamic economics?. In this thesis, the researcher employs a qualitative research method. Qualitative research is a procedure that produces descriptive data in the form of written or spoken words from people and observed behaviors. To collect data, the researcher uses interview and observation techniques. Data analysis is carried out through data reduction, data presentation, and data verification. Based on this orientation, the research findings indicate that the risks faced by Swalayan Al-Fatih include internal risks such as conflicts among employees, lack of skills, and low employee loyalty. External risks, such as intense competition, unsold products, as well as environmental and natural factors, were also identified. In conclusion, the risk management strategy according to Islamic economics is based on the Qur'an and Hadith, as taught by Prophet Muhammad SAW. The strategy implemented by Swalayan Al-Fatih meets several criteria of Islamic economics.